2022
DOI: 10.3389/fpubh.2022.904374
|View full text |Cite
|
Sign up to set email alerts
|

Can Self-Regulatory Strength Training Counter Prior Mental Exertion? A Systematic Review of Randomized Controlled Trials

Abstract: BackgroundPrior mental exertion consumes self-regulation and influences any subsequent physical or cognitive performance according to the strength model of self-regulation. However, the counteractive effect of self-regulatory strength training remains unclear.ObjectiveThis study aims to report a comprehensive systematic review investigating self-regulatory strength training programmes on physical or cognitive performance.MethodsTo select relevant studies from the available literature, a thorough search was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…In a manner that is consistent with Sun and Soh [ 17 ], the current review also showed that self-regulatory strength training programs can significantly enhance cognitive and physical performance after mental exertion (see Table S5 ). Furthermore, the current review highlights the conservation hypothesis regarding the controversy of the role of motivation in self-regulation.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In a manner that is consistent with Sun and Soh [ 17 ], the current review also showed that self-regulatory strength training programs can significantly enhance cognitive and physical performance after mental exertion (see Table S5 ). Furthermore, the current review highlights the conservation hypothesis regarding the controversy of the role of motivation in self-regulation.…”
Section: Discussionsupporting
confidence: 85%
“…Sun and Soh [ 17 ] corroborated the “global” hypothesis in the strength model of self-regulation from the finding of the cross-domain effect of strength -based training programs. The findings of the current review could further explain and prove the cross-domain effect of the other three ingredients of the self-regulation process.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It is worthy to note that although the resource model is the best-known model of self-regulation so far, it may be manipulated to counter prior mental exertion (e.g., mental fatigue and ego depletion) ( Sun et al, 2022b ). However, it has met many challenges in the recent decade ( Inzlicht and Schmeichel, 2012 ; Inzlicht et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The consideration of possible covariance was largely absent in the included studies, such as the trait of self-control, which has been recognized as an ability to manage finite cognitive resources (49,50). The most recent study showed that these finite resources may have a counteractive effect on mental fatigue (51). Although mental fatigue is a "state" condition, it is crucial to control this "trait" for future investigation, because it might be a factor that influences the degrees of mental fatigue.…”
Section: Study Limitations and Recommendations For Future Studiesmentioning
confidence: 99%